2020
DOI: 10.1007/s40688-020-00302-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Autism/ASD Among Preschool and School-age Children in Norway

Abstract: In recent years, there has been a considerable rise in prevalence rates for autism/autism spectrum disorders (ASD) around the globe. Understanding the patterns of prevalence is essential for policy development at national and local levels that effectively plans for medical, psychological, behavior analytical, and educational interventions. This study presents new data on the prevalence of ASD among preschool and school-age children (ages 1-16 years) in Norway. Based on the International Classification of Disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…Specifically, the number of male patients included in this study is greater than that of female patients. Previous studies also reported a high prevalence of autism and ADHD in males (Ayano et al, 2020;Morales-Hidalgo et al, 2018;Özerk & Cardinal, 2020). Second, we did not assess the severity of the children's illnesses.…”
Section: Limitationsmentioning
confidence: 91%
“…Specifically, the number of male patients included in this study is greater than that of female patients. Previous studies also reported a high prevalence of autism and ADHD in males (Ayano et al, 2020;Morales-Hidalgo et al, 2018;Özerk & Cardinal, 2020). Second, we did not assess the severity of the children's illnesses.…”
Section: Limitationsmentioning
confidence: 91%
“…Although the prevalence of ASD varies by country, it is on the rise overall. 6 16 17 An increased prevalence means that there is an increased number of newly diagnosed cases if the mortality rate is consistent. The United States established the Autism and Developmental Disabilities Monitoring Network in 2000.…”
Section: Discussionmentioning
confidence: 99%
“…The 5th edition of DSM is currently used as a basis for the diagnosis of autism by developmental pediatricians. Recent demographics show a global increase in the rate of children with autism (Qiu et al, 2020;Özerk & Cardinal, 2020). In the Philippines, more than one million children have autism (Lambatin, 2018), and some are not identified and diagnosed.…”
Section: Literature Review Autism Spectrum Disordermentioning
confidence: 99%